1983
DOI: 10.1002/qj.49710946111
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory studies of the charging of soft‐hail during ice crystal interactions

Abstract: A laboratory investigation of electric charge transfer during the impact of vapour-grown ice crystals and supercooled water droplets upon a simulated soft-hailstone target has shown that the magnitude of the charge transferred to the riming surface when crystals separate from it is a function of temperature, crystal dimension, relative velocity, liquid water content, and impurity content of the water droplets and hence the impurity content of the riming target. The sign of the charge transfer depends on temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
146
0
4

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 377 publications
(162 citation statements)
references
References 28 publications
12
146
0
4
Order By: Relevance
“…graupel or hail pellets) that collide with ice crystals in a suspension of supercooled water droplets (Reynolds et al, 1957;Takahashi, 1978;Berdeklis and List, 2001;Adamo et al, 2007). Laboratory studies by Takahashi (1978) and Jayaratne et al (1983) also showed that the charge sign is positive or negative as a function of the cloud temperature and liquid water content (LWC). Further laboratory studies have investigated the impact of cloud conditions on electrification (see Saunders et al, 2006), which also underline the importance of mixing solid and liquid hydrometeors.…”
Section: Introductionmentioning
confidence: 99%
“…graupel or hail pellets) that collide with ice crystals in a suspension of supercooled water droplets (Reynolds et al, 1957;Takahashi, 1978;Berdeklis and List, 2001;Adamo et al, 2007). Laboratory studies by Takahashi (1978) and Jayaratne et al (1983) also showed that the charge sign is positive or negative as a function of the cloud temperature and liquid water content (LWC). Further laboratory studies have investigated the impact of cloud conditions on electrification (see Saunders et al, 2006), which also underline the importance of mixing solid and liquid hydrometeors.…”
Section: Introductionmentioning
confidence: 99%
“…The time-height graupel mixing ratio and number concentration (Fig. 4b) show a maximum (Jayaratne et al 1983;Gardiner et al 1985;Ziegler et al 1991). The reversal temperature (for CWC > 0.1 g m -3…”
Section: Dynamic and Microphysics Evolutionmentioning
confidence: 92%
“…Since the non-inductive charge separated during collisions between ice-phase particles generally depends on temperature, the relative velocity of the collisions, hydrometeor concentration and the supercooled droplet size spectrum (Takahashi 1978;Jayaratne et al 1983;Gardiner et al 1985;Saunders et al 1991;Brooks et al 1997;Saunders and Peck 1998), the contributions of the non-inductive charging process to electrification in these four cases are the same. The time evolution of the non-inductive charging rate is presented in Fig.…”
Section: Charging Ratementioning
confidence: 99%
See 1 more Smart Citation
“…In the first stage, macroscopic particles are electrically charged, and in the second stage particles of different polarity are separated by gravitation or other (mechanical) forces; in order to separate particles with different polarities, these forces need to be stronger than the electric attraction between charges of different polarity, since otherwise the electric forces would counteract the growth of the electric field. The possible charging mechanisms at work within normal terrestrial thunderclouds are reviewed, e.g., by Jayaratne et al (1983) and Saunders (2008). An important conclusion of these reviews is that charge is efficiently separated between particles only in direct collisions.…”
Section: Thundercloud Electrification Lightning and Transient Luminomentioning
confidence: 99%